Bilateral Nephroblastomatosis With a Unilateral Wilms Tumor: A Case Report Highlighting Imaging Characteristics - Amine Naggar MD; Saad Assila MD; Khadija Laasri MD; Hajar Andour MD; Zineb Izi MD; Najat Lamalmi PhD; Siham El Haddad PhD; Nazik Allali PhD; Latifa Chat PhD (SAGE Publishing, 2024)
Nephrogenic rests (NRs) are foci of embryonic nephrogenic cells that persist beyond the 36th week of gestation. They are precursor lesions of Wilms tumor and are found incidentally in approximately 1% of infants. The term nephroblastomatosis (NBS) is utilized when nephrogenic rests extensively or multifocally affect the kidneys. We report a case of a left nephroblastoma with bilateral nephroblastomatosis, treated with neoadjuvant chemotherapy followed by a left nephrectomy, highlighting the imaging features of nephrogenic rests on ultrasound, CT, and MRI, and the potential possibilities of distinguishing nephroblastomas from nephrogenic rests in one hand, and the possibilities of distinguishing active nephrogenic rests from inactive ones in the other hand. We furthermore discuss the role of histology in making those distinctions, and the role of chemotherapy in reducing nephrogenic rests' size and cellularity.